Determinan pertumbuhan ekonomi berkelanjutan wilayah induk dan pemekaran di kawasan timur Indonesia - Dinar Melani Hutajulu; Jihad Lukis Panjawa; Fitrah Sari Islami; RR Retno Sugiharti (Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2020)
This study aims to evaluate the determinants of economic growth in the Eastern Indonesia Region after the government implemented the regional autonomy policy in Indonesia. This research covers the original regions and the expansion regions of the Eastern Indonesia Region. This study uses the secondary data from Statistics Indonesia (Badan Pusat Statistik). This study uses cross-sectional data in 2017 that covers 230 districts and cities. This study uses the least square dummy variable in analyzing the data. The analysis shows that there is no difference in economic growth between the original regions and the expansion regions. However, these two regions exhibit different results of the effects of poverty, human development, inequality, and fiscal decentralization on economic growth. In the original regions, the variables of poverty, human development, and fiscal decentralization affect economic growth. Meanwhile, in the expansion regions, only the variables of human development and fiscal decentralization have impacts on the economic growth.